PENGARUH KUALITAS PRODUK DAN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN - Adi Santoso (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2016)
This study aims to examine and analyze the effect of variable product quality , brand image, brand trust and brand loyalty to the purchasing decision. To test these variables, researchers used male and female students who have a Mobile Samsung in scope Semarang Sultan Agung Islamic University as a research object. This study uses 100 respondents where sampling is done by using a quota sampling technique. The results showed that the quality of the product and brand trust and significant positive effect on brand loyalty and purchasing decisions while brand image has no significant effect on brand loyalty and purchasing decisions and brand loyalty is positive and significant impact on consumer purchasing decisions .